Analysis of Factors Affecting Surplus Underwriting of Sharia General - Nasution, Siska Amelia; Ramadhani, Sri; Nasution, Juliana (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The purpose of this study is to determine whether participant contributions, investment returns, and underwriting claim surplus all have a substantial effect, both separately and in combination. This study uses qualitative descriptive techniques in addition to secondary data collected from 2019–2022 financial statements and other publications. In Indonesia, sharia general insurance and sharia general insurance units provide protection for the community. Thirteen sharia general insurance companies that met the previously determined sample requirements were selected as samples. Panel data examination uses multiple linear regression. Additionally, the competitive landscape of the insurance market plays a crucial role in shaping underwriting outcomes. This research contributes to the understanding of how various internal and external factors affect the financial health of Sharia general insurance providers. The results provide valuable insights for practitioners and policymakers aiming to enhance the performance of Sharia insurance products. Recommendations for improving surplus underwriting practices are also discussed, emphasizing the importance of education and regulatory support in fostering a robust Sharia insurance sector.